Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Nonfisik Terhadap Kinerja Karyawan Pada Toko Indomaret Area Pluit Jakarta Utara - Heri Yulianto; Sonny Sonny (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is. To determine the influence of leadership style and non- physical work environment partially and simultaneously on employee performance at the Indomaret Store in Pluit Area, North Jakarta. This research method uses a quantitative descriptive method, data collection techniques using questionnaires. The population is 67 employees, sampling can use saturated sampling, so the sample is all employees totaling 67 employees. Data analysis uses validity test, reliability test, classical assumption test, multiple regression analysis, multiple correlation coefficient analysis, determination coefficient analysis and hypothesis test. From the table above, the results of the calculation of the t-test value of the Leadership Style variable (X1) with a t count of 8.353 and a significance of 0.000. It is said to be positive if the calculated t is greater than the t table (8.353 > 1.996) and the significance if it is less than (0.05 < 0.000) then Ha is accepted and H0 is rejected, it can be stated that Leadership Style (X1) partially has a significant effect on Employee Performance (Y) and produces an R Square value of 0.695 or 69.5% while the rest is 30.5%. Based on the results of the calculation of the Non-Physical Work Environment t test (X2) with a calculated t of 11.019 and a significance of 0.000. It is said to be positive if the calculated t is greater than the t table (11.019 > 1.996) and the significance if it is less than (0.05 < 0.000) then Ha is accepted and H0 is rejected, it can be stated that the Non-Physical Work Environment (X2) partially has a significant effect on Employee Performance (Y) and produces an R Square value of 0.780 or 78% while the rest is 22%. Based on the results above, namely the ANOVA test, the Fcount value is 272.155 while the Ftable (   0.05) for n = 64 is 2.75. So Fcount> Ftable (0.05) or 272.155> 2.75, with a significant level of 0.000 because 0.000 <0.05, it can be said that Leadership Style (X1), Non-Physical Work Environment (X2) and together have an effect on Employee Performance (Y) and produce an R Square value of 0.895 or 89.5% while the rest is 10.5%.